2022
DOI: 10.3390/ani12030348
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Links between the Endocannabinoidome and the Gut Microbiome, with Special Reference to Companion Animals: A Nutritional Viewpoint

Abstract: There is growing evidence that perturbation of the gut microbiome, known as “dysbiosis”, is associated with the pathogenesis of human and veterinary diseases that are not restricted to the gastrointestinal tract. In this regard, recent studies have demonstrated that dysbiosis is linked to the pathogenesis of central neuroinflammatory disorders, supporting the existence of the so-called microbiome-gut-brain axis. The endocannabinoid system is a recently recognized lipid signaling system and termed endocannabino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 193 publications
0
12
0
Order By: Relevance
“…Although studies in small animals are still scarce, there is growing evidence that endocannabinoid-like ALIAmides play key roles in the health of different body organs, such as the gastrointestinal tract [ 113 , 114 ] and the nervous system [ 32 , 34 , 37 ], as well as the upper and lower urinary tract [ 115 , 116 , 117 , 118 ] and the musculoskeletal system [ 97 , 119 , 120 ]. In addition, the deep involvement of ALIAmides in obesity-induced metainflammation is becoming increasingly evident [ 69 , 113 , 121 , 122 , 123 ].…”
Section: Preclinical and Clinical Results In Small Animalsmentioning
confidence: 99%
“…Although studies in small animals are still scarce, there is growing evidence that endocannabinoid-like ALIAmides play key roles in the health of different body organs, such as the gastrointestinal tract [ 113 , 114 ] and the nervous system [ 32 , 34 , 37 ], as well as the upper and lower urinary tract [ 115 , 116 , 117 , 118 ] and the musculoskeletal system [ 97 , 119 , 120 ]. In addition, the deep involvement of ALIAmides in obesity-induced metainflammation is becoming increasingly evident [ 69 , 113 , 121 , 122 , 123 ].…”
Section: Preclinical and Clinical Results In Small Animalsmentioning
confidence: 99%
“…Many bioactive lipids regulate several physiological processes that maintain the gut-barrier integrity, control inflammation, pain and energy metabolism (see ( 49 ) for a comprehensive review). OEA in particular exerts prominent roles in intestinal physiology; it reduces intestinal motility together with other lipid mediators such as PEA and oleamide, suggesting a potential target for the development of efficient drugs to reduce intestinal motility ( 50 ); OEA presumably partakes in the maintenance of normal glucose homeostasis as it increases the secretion of Glucagon-like Peptide-1 (GLP-1, an intestinal hormone with potent insulinotropic effects) by binding to GPR119 expressed on enteroendocrine L-cells ( 51 ).…”
Section: Oea Is a Predominant Player In Intestinal Physiologymentioning
confidence: 99%
“…There is no doubt that the microbiota affects gut physiology and its role in the gut brain-axis has been convincingly established ( 75 ). Many physiological roles of intestinal microorganisms are associated to the regulation of the intestinal endocannabinoid tone [the so called endocannabinoidome ( 49 ) as extensively described in recent exhaustive reviews ( 76 78 ). There is increasing evidence that both selected intestinal microorganisms and bioactive lipids covary in pathological conditions such as obesity, type 2 diabetes and inflammation ( 76 ).…”
Section: Intestinal Microbiota Interactions With the Endoca...mentioning
confidence: 99%
“…The eCB system is comprised of endogenous lipids that trigger specific G protein-coupled receptors termed cannabinoid receptors 1 and 2 (CB1 and CB2). It has been demonstrated that the eCB system consists of more than 100 lipid mediators and 50 proteins, such as CB1, CB2, N-arachidonoylethanolamine (AEA), 2-arachidonoyi-glycerol (2-AG), and the anabolic and catabolic enzymes for the endocannabinoids (146,147). The eCB system has the ability to regulate gut-barrier function, gut permeability, and metabolic endotoxemia in obesity, and control energy balance by manipulating the metabolic process, energy intake and fat accumulation in adipocytes (148)(149)(150).…”
Section: Endocannabinoid Systemmentioning
confidence: 99%
“…found chronic N -oleoyl-ethanolamine (OEA) administration to mice in normal diet could shift Firmicutes/Bacteroides ratio, decrease Lactobacillus , and reduce intestinal cytokines expression ( 153 ). In obese humans, supplementation of OEA decreased BMI and waist circumference, which might due to the activation of PPARα ( 147 ). And the administration of palmitoyl ethanolmaide (PEA), which is a member of N -acyl ethanolamide (NAE) similar to AEA, could decrease body weight, food intake, and fat mass in HFD rats ( 154 ).…”
Section: Factors Mediate the Cross-talk Between Gut Microbiota And Ad...mentioning
confidence: 99%